Characterisation of the human α2(I) procollagen promoter-binding proteins - Collins, Malcolm Robert (Division of Medical Biochemistry and Structural Biology, 2018)
In an attempt to elucidate the transcriptional mechanisms that regulate the expression of the human α2(I) procollagen gene, cis-acting DNA-elements within the proximal promoter were identified and their corresponding trans-acting factors characterised. The fibroblast cell lines used in this study had previously been transformed with either simian virus 40 (SVWI-38) or by γ-radiation (CT-1). The SVWI-38 fibroblasts do not produce any α2(I) collagen chains, whereas the CT-1 cell line produces normal type I collagen. Previous studies suggested that trans-acting factor(s) may be responsible for the inactivation of the α2(I) procollagen gene in SVWI-38 fibroblasts (Parker et. al. (1989) J. Biol. Chem 264, 7147-7152; Parker et. al. (1992) Nucleic Acids Res. 20, 5825-5830). In this study, the SVWI-38 proximal promoter (-350 to +54) was sequenced and shown to be normal, thereby ruling out any possibility that mutations within this region was responsible for inactivation of the gene.